Thyroid Hormone Deficiency Modifies Hepatic Lipid Droplet Morphology and Molecular Properties in Lithogenic-Diet Supplemented Mice - Kube, Irina; Jastrow, Holger; Führer, Dagmar; Zwanziger, Denise (Experimental and Clinical Endocrinology & Diabetes, 2021)
Objective Thyroid hormones have been associated with a hepatic lipid lowering effect and thyroid function has been shown to play a substantial role in development of non-alcoholic fatty liver disease. Hepatic lipid droplets differ in the number, size and molecular properties depending on metabolic state or pathological condition. However, in how far thyroid hormone deficiency affects hepatic lipid droplet morphology and molecular properties is still poorly understood. Therefore, we performed a study in mice using a lithogenic diet model of steatohepatitis and modulated the thyroid hormone status.Methods Male and female three months old C57BL/6 mice were divided into a euthyroid (control), a lithogenic (litho) and a lithogenic+thyroid hormone deficient (litho+hypo) group and treated for six weeks. Hepatic transmission electron microscopy and gene expression analysis of lipid-droplet associated proteins were performed.Results Increased mean diameters of hepatic lipid droplets and a shift towards raised electron-density in lipid droplets was observed under thyroid hormone deficiency. Furthermore thyroid hormone deficiency altered hepatic expression of genes involved in lipophagy and triacylglycerol mobilization. Interestingly, while the impact of thyroid hormone deficiency on lipid droplet morphology seems to be sex-independent, hepatic lipid droplet-associated gene expression differed significantly between both sexes.Conclusion This study demonstrates that thyroid hormone deficiency alters hepatic lipid droplet morphology and hepatic gene expression of lipid droplet-associated proteins in a lithogenic diet mouse model of steatohepatitis.
Keywords: thyroid dysfunction; lipid droplets; hepatocytes; hepatic lipid accumulation; metabolic liver diseases